Regioselectivity switch: gold(I)-catalyzed oxidative rearrangement of propargyl alcohols to 1,3-diketones - Hashmi, A. Stephen K.; Wang, Tao; Rudolph, Matthias (The journal of organic chemistry, 2012)
The gold(I)-catalyzed oxidative rearrangement of propargyl alcohols provides an eﬃcient and selective route to 1,3-diketones under mild conditions. Pyridine-N-oxides were used as external oxidants with, diﬀerent from related substrates, no alkylidenecycloalkanones or oxetan-3ones formed as side-products.